The Effect of Wind Loading on the Growth of Crack Propagation in Aircraft Wing - Subhi, Shahad Nashat; Al-shamma, Fathi (Al-Nahrain Journal for Engineering Sciences, 2025)
Throughout the flight, aircraft wings continuously struggle against various forces: the forward thrust from the engine, the drag pulling them backward, and sudden turbulence from storms. In contrast, these forces are essential for maintaining aircraft stability. With time, the cyclic stresses can result in the formation and propagation of minuscule cracks in the wings. Cracks growing on the aircraft wing surface manufactured from alloy AL7075-T6, have been investigated when subjected to non-preoperational multi-axial cyclic loading. The results have been evaluated using two methods, numerical simulations and theoretical calculation to evaluate dynamic crack propagation crack growth per cycle (da/dN) at angles of attack 5° and 10°. The results showed that the dynamic crack propagation increases with an increase in the crack length. It was found that the values of the dynamic crack propagation rate at the angle of attack 5⁰ are smaller than the values at the angle of attack 10⁰.